How Low is Low Enough to be Given Testosterone Replacement Therapy in Patients with Late Onset Hypogonadism? What Should Be Evaluated? A Case Report - Geraldo Laurus; Supardi (Indonesian Andrology and Biomedical Journal, 2022)
Abstract Background: Late Onset Hypogonadism (LOH) is a disease associated with advancing age, characterized by symptoms and a deficiency in serum testosterone. It is important to choose which patient suitable for testosterone replacement therapy (TRT), but there is no one consensus that fits for all. After treating patients with testosterone replacement therapy (TRT), several parameters need to be evaluated. Case: A 74-years old male came with chief complaint of difficulty to maintain erection since 2 years ago.. PADAM questionnaire was positive and IIEF-5 score was 6. Physical examination showed an underweight condition. Total testosterone level was 3,65ng/mL, and patient chose to be given TRT instead of evaluating his free testosterone. PDE-5 inhibitor and non-pharmacologic treatment was also given. Follow-up showed that his erection was improved. Discussions: At which level should testosterone be substituted is still debatable. Several consensuses issued by several organization still cannot be used universally. Study in Indonesia showed that symptoms of LOH had been occur when the testosterone level still in normal range. After giving TRT to our patients, routine follow up is needed. Non pharmacologic treatment also needs to be addressed to improve the outcome. Conclusions: Symptoms of LOH had been occurred even though testosterone level is still in normal range. The consideration made by clinician is the most important thing to be evaluated, whether to give TRT or not. Somatic and laboratory parameters mentioned in this study is important to be evaluated.